HIV-1 infection among crack cocaine users in a region far from the epicenter of the HIV epidemic in Brazil: Prevalence and molecular characteristics. - Divânia Dias da Silva França; Nativa Helena Alves Del-Rios; Megmar Aparecida Dos Santos Carneiro; Rafael Alves Guimarães; Karlla Antonieta Amorim Caetano; Monica Nogueira da Guarda Reis; Regina Maria Bringel Martins; Ana Rita Coimbra Motta-Castro; Mariane Martins de Araujo Stefani; Sheila Araujo Teles (PLoS ONE)
Brazil has the largest cocaine market in South America, and crack cocaine use is closely associated with HIV-1 infection. This study investigated the prevalence, risk factors, and HIV-1 subtypes, including recombinant forms and mutations associated with drug resistance, among crack cocaine users in Central-West Brazil. We recruited 600 crack cocaine users admitted to a referral hospital in Goiânia for psychiatric disorders. The participants were interviewed; blood samples were collected for anti-HIV-1/2 serological screening. HIV-1 pol gene sequences (entire protease [PR] and partial reverse transcriptase [RT]) were obtained from plasma RNA. HIV-1 subtypes, recombinant viruses, transmitted drug resistance (TDR), and secondary drug resistance mutations were investigated. The median participant age was 30 years (range, 18-68 years); most were male, single, unemployed, and of mixed races. Among them, 2.8% (17/600) were HIV-1 positive: 2.2% of men (11/507) and 6.5% of women (6/93). The main predictors of HIV-1 seropositivity were a sexual partner with HIV infection, irregular condom use, and previous homelessness. HIV-1 pol sequences (12/17) indicated the predominance of subtype B (n = 7), followed by recombinant forms FPR/BRT (n = 1) and BPR/FRT (n = 2) and subtypes F1 (n = 1) and C (n = 1). TDR prevalence was 58.3% (7/12). Isolates from two participants showed mutations associated with resistance to nucleoside reverse transcriptase inhibitors (NRTI) only (M41L, T125C, T125F, M184V), while an isolate from one patient who had received antiretroviral therapy (ART) since 2008 had a mutation associated with resistance to non-NRTI (G190S). Five isolates had secondary mutations to protease inhibitors (K20M, L10V, L33I, A71T, A71V). In conclusion, the findings of HIV-1 circulation, TDR to NRTI, and secondary mutations to protease inhibitors in ART-naïve crack cocaine users support the importance of monitoring this population in regions far from the epicenter of the HIV epidemic.